The handbook of histopathological practices in aquatic environments : guide to histology for environmental toxicology - Costa, Pedro Moura (Academic Press, an imprint of Elsevier, 2017)
"[This work] offers readers in aquatic biology and other water-based environmental sciences a comprehensive resource on histopathology, which is a key tool in the growing field of ecotoxicology. This work brings together the necessary knowledge, from sample preparation, to trait identification, and scoring and data treatment. Furthermore, with examples from several groups of organisms (from worms to fish), these practices can be applied across a wide array of aquatic ecosystems. This book provides a step-by-step approach to solving the questions researchers encounter in aquatic biology and related fields."--Https://www.elsevier.com